Peran Perbankan Syariah terhadap UMKM Selama Pandemi Covid-19 (Studi Kasus Bank Syariah Indonesia KC Medan) - Nasrun Ritonga; Riny Viri Insy Sinaga (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2021)
Bank Syariah Indonesia performs the function of a bank as a place to save and distribute funds from the public to assist development in Indonesia. The existence of a bank is also highly dependent on the public's trust. The higher the public trust, the higher the public awareness to save their money in the bank and use other services from the bank. Small and medium enterprises (MSMEs) are one of the leading driving forces in the development of the manufacturing industry. The movement of the MSME sector is vital for creating economic growth and employment. This study aims to determinethe role of Islamic banking in MSME actors during the COVID-19 pandemic, this research was conducted at Bank Syariah Indonesia KC Ahmad Yani Medan. Research is using the methods of descriptive kualitatif and data used are primary data. Instruments that are used in primary data. Instruments that are used in primary data are interviews with speakers from Bank Syariah Indonesia KC Ahmad Yani Medan. From the research it can be known that Bank Syariah Indonesia KC Ahmad Yani Medan helped distribute the programs of government, namely Kredit Usaha Rakyak (KUR) to encourage perpetrators of MSMEs in future pancemic, wirh the help of customers who already receive disbursement of funds financing before a pandemic to provide relaxation or relief from paying installments.